Piloting the climate smart agriculture – Multistakeholder platform development guideline: Experience from Adama Woreda in Ethiopia - Assefa, Berhanu; Tesfaye, Lidya; Jalango, Dorcas; Ndetu, Veronica; Binge, Brenda (2025)
The Climate-Smart Agriculture Multi-Stakeholder Platform (CSA-MSP) guideline (developed by the Alliance of Bioversity International and CIAT in collaboration with the Ministry of Agriculture and Livestock Development – Kenya, and the Ministry of Agriculture – Ethiopia) provides a practical framework for establishing functional, inclusive, and coordinated mechanisms that support the implementation of climate-smart agriculture at national and sub-national levels. Recognizing the interlinked challenges of climate change, food security, and sustainable agricultural development, the guideline draws on global best practices and lessons from countries like Kenya and Ethiopia, where the Kenya CSA-MSP and Ethiopia CSA Forum, respectively, have been established to facilitate participatory decision-making, knowledge sharing, and policy alignment.